2019
DOI: 10.1007/s00392-019-01577-w
|View full text |Cite
|
Sign up to set email alerts
|

Strain analysis reveals subtle systolic dysfunction in confirmed and suspected myocarditis with normal LVEF. A cardiac magnetic resonance study

Abstract: Number 39 42 Males 33 33 0,98 Age [years] 35 (28-43) 35 (28-43) 0,98 Height [cm]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…13,14 In a study by Kostakou et al, 15 it was suggested that in patients with acute myocarditis and normal LV-EF, the left ventricular global longitudinal strain (LV-GLS) is lower than that in a healthy control group. Porcari et al 16 focused on patients with acute myocarditis, normal LV-EF, and negative LLC and showed significantly impaired strain values (including LV and RV) in patients with both suspected and confirmed acute myocarditis (negative and positive LLC, respectively), but the prognostic value was not addressed.…”
mentioning
confidence: 99%
“…13,14 In a study by Kostakou et al, 15 it was suggested that in patients with acute myocarditis and normal LV-EF, the left ventricular global longitudinal strain (LV-GLS) is lower than that in a healthy control group. Porcari et al 16 focused on patients with acute myocarditis, normal LV-EF, and negative LLC and showed significantly impaired strain values (including LV and RV) in patients with both suspected and confirmed acute myocarditis (negative and positive LLC, respectively), but the prognostic value was not addressed.…”
mentioning
confidence: 99%
“…34 Once images are acquired, specific software are utilized for their postprocessing analysis. 36 In 2009, the original LLC were established and then updated in 2018. The LLC suggest a "2 out of 2" approach in an attempt to increase the accuracy in detecting acute myocarditis.…”
Section: Cmr Prerequisites and Technical Approachmentioning
confidence: 99%
“…Moreover, global CS is more accurate than global LS in characterizing acute myocarditis affecting the RV. 36 Among circumferential, longitudinal, and radial strain (RS), the latter (which represents the shortening of subendocardial longitudinal fibers) usually is the last resulting impaired in a number of different settings. Because of that, RV is important in the last stages of myocarditis but of limited relevance in the early phases of the same.…”
Section: Future Imaging Directions: Myocardial Strainmentioning
confidence: 99%
“…This information needs to be integrated in a multiparametric evaluation, considering traditional as well as novel prognostic indexes. NYHA class, ECG, LVEF, right ventricular function [130], diastolic function [131], mitral regurgitation [132], deformation imaging [133], and serum biomarkers (i.e., NTpro-BNP) are fundamental instruments to stratify the risk of events as they reflect the functional status of patients, the degree of biventricular derangement, the hemodynamic impairment, and the magnitude of neurohumoral activation. The change of these indicators over time along with the ventricular arrhythmic burden is an additional element to consider [134].…”
Section: Cmr In Prognostic Stratificationmentioning
confidence: 99%